2 Peter and Jude : A Handbook on the Greek Text - Davids, Peter H (Waco, Tex. : Baylor University Press, 2011)
"This new installment of the popular handbook series gives teachers and students a comprehensive guide to the grammar and vocabulary of both 2 Peter and Jude. Within the text of these intertwined Catholic Epistles, Peter H. Davids finds rhetorical features and stylistic elements often overlooked. By using this handbook in combination with traditional commentaries, students will be guided toward a greater understanding of the Greek text in 2 Peter and Jude while gaining a deeper appreciation for textual and rhetorical intricacies not available in the English translations" -- Publisher description
Includes bibliographical references and indexes
Keywords: Bible. -- Criticism, Textual; Bible. -- Versions; Bible. -- Criticism, Textual; Bible. -- Versions; Second Peter and Jude - Interpretation - Greek Text